“I Think You Think I Think You're Lying”: The Interactive Epistemology of Trust in Social Networks - Moldoveanu, Mihnea C.; Baum, Joel A. C. (Management Science, 2011)
We investigate the epistemology of trust in social networks. We posit trust as a special epistemic state that depends on actors' beliefs about each others' beliefs as well as about states of the world. It offers new ideas and tools for representing the core elements of trust both within dyads and larger groups and presents an approach that makes trust measurable in a noncircular and predictive, rather than merely postdictive, fashion. After advancing arguments for the importance of interactive belief systems to the successful coordination of behavior, we tune our investigation of trust by focusing on beliefs that are important to mobilization and coordination and show how trust functions to influence social capital arising from network structure. We present empirical evidence corroborating the importance of higher-order beliefs to understanding trust and the interactive analysis of trust to the likelihood of successful coordination. This paper was accepted by Jesper Sørensen, organizations and social networks.